Salsa-J - Anne-Laure Melchior (Zenodo, 2018)
SalsaJ is free, student-friendly software developed specifically for the EU-HOU project (http://www.euhou.net/). SalsaJ is designed to be easy to install and use. It allows students to display, analyse, and explore real astronomical images and other data in the same way that professional astronomers do, making the same kind of discoveries that lead to true excitement about science. A number of exercises have developed complete with data to download and detailed instructions for use. The flexibility of the SalsaJ tool enables students and teachers to extend the exercises with their own observations. SalsaJ is multi-platform and multi-lingual : SalsaJ has been translated into many languages: English, French, Spanish, Italian, Polish, Greek, Portuguese, Swedish, Northern Sami, Arabic, Chinese. Its design enables easy implementation and requires virtually no on-site maintenance.The software can be downloaded by clicking here. (www.euhou.net/index.php/salsaj-software-mainmenu-9/download-mainmenu-10?task=view&id=8) Description retreived from: http://www.euhou.net/index.php/salsaj-software-mainmenu-9?task=view&id=7